Resistance exercise training restores bone mineral density in renal transplant recipients - Eatemadololama, Ali (Clin Cases Miner Bone Metab, 2017)
BACKGROUND: The kidneys are complex organs of human body sustain a number of vital and important functions. These organs need to be replaced in some subjects due to various diseases. Bone mineral density (BMD) of the subjects with kidney transplantation reduced as a result of poor mobility and use of especial drugs. Due to lack of information regarding the influences of weight training exercise on BMD of long bone, this research was done. METHOD: 24 subjects with history of kidney transplantation were recruited in this study. They were divided into two groups who received weight training exercise and control group. The BMD of femur and lumbar spine was measured by use of dual energy X-Ray absorptiometry in both groups. The difference between BMD was evaluated by use of two sample T test. RESULT: The mean values of BMD of femur were 0.679±0.09 g/cm(2) and 0.689±0.09 before and after exercise in this first group. In contrast it was 0.643±0.11 before follow-up and 0.641±0.11 g/cm(2) after follow-up in the control group. There was no difference in BMD of lumbar spine after exercise. CONCLUSION: The result of this research study showed that BMD of long bone improved follow exercise. Therefore, it was concluded that weight training exercise can be used for the subjects with kidney transplantation.